Control interno y ejecución presupuestal de la Municipalidad Distrital de Parinari, Loreto 2022 - Cardenas Amasifuen, Yowys Adler Vam (2024)
The general objective of this research was to determine the influence of internal control in the budget execution of the District Municipality of Parinari, Loreto 2022. Regarding the methodology, the type of research was quantitative with an explanatory-correlational design, the population and sample consisted of 50 workers of the entity and the budget reports, for which questionnaires, observation form and documentary analysis guide were used for data collection. Results: The internal control of the municipality is regular according to what was expressed by 44.0% of the collaborators, since the deficiencies are not significant because 55% of the activities that make up the components of this control have been executed in an efficient, timely and transparent manner; on the other hand, the level of budget execution is high given that the percentage of progress recorded for budget expenditures and revenues was represented by 86.0% and 84.6% respectively. Conclusion: Internal control has a significant influence on the entity's budget execution because the correct development of the activities of the control components contributes to the efficient and timely use of budgetary resources.